Prevalence of Pulmonary Hypertension and its Influence on Survival in Patients With Advanced Chronic Obstructive Pulmonary Disease Prior to Lung Transplantation. (2nd January 2016) - Hayes, Don; Black, Sylvester M.; Tobias, Joseph D.; Mansour, Heidi M.; Whitson, Bryan A.
Abstract: Introduction : Prevalence of pulmonary hypertension (PH) and its influence on survival in chronic obstructive pulmonary disease (COPD) are not well studied in the lung allocation score (LAS) era. Methods : The UNOS database was queried from 2005 to 2013 to identify first-time adult lung transplant candidates with COPD who were tracked from wait list entry date until death or censoring to determine both prevalence and influence of PH. Using right heart catheterization measurements, mild PH was defined as mean pulmonary artery pressure (mPAP) ≥ 25 mmHg and severe ≥ 35 mmHg. Results : Of 1315 COPD candidates not transplanted, 1243 were used for survival analysis using Cox proportional hazards models, and 1010 (mild PH) and 244 (severe PH) were used for propensity score matching, respectively. A total of 52% (652) of subjects had PH mPAP ≥ 25 mmHg. Univariate analysis revealed significant differences in survival for mild PH (HR = 1.769; 95% CI: 1.331, 2.351; p < 0.001) and severe PH (HR = 3.271; 95% CI: 2.311, 4.630; p < 0.001). Kaplan–Meier survival function demonstrated significant disparities for mild PH (Log-rank test: Chi-square1 : 15.87, p < 0.0001) and severe PH (Log-rank test: Chi-square1 : 50.13, p < 0.0001). Multivariate Cox models identified significant risk for death for mild PH (HR = 1.987; 95% CI: 1.484, 2.662; p < 0.001) and severe PH (HR = 3.432; 95% CI: 2.410, 4.888; p < 0.001). Propensity score matching confirmed increased mortality hazard associated with mild PH (HR = 2.280; 95% CI: 1.425, 3.649; p = 0.001) and severe PH (HR = 7.000; 95% CI: 2.455, 19.957; p < 0.001). Conclusions : PH is highly prevalent in advanced COPD and associated with a significantly higher risk for mortality.